2005
DOI: 10.1111/j.1365-2907.2005.00067.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecological impact of beaversCastor fiberandCastor canadensisand their ability to modify ecosystems

Abstract: 1.The genus Castor comprises two species: the Eurasian beaver Castor fibre , and the North American beaver Castor canadensis . Both species suffered from overexploitation, but have seen a revival since the 1920s due to increased protection and reintroduction programmes. Increases in the populations and distributions of species that are able to modify ecosystems have generated much scientific interest. Here we review the available literature concerning the possible ecological impact of beaver species in the Old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
466
0
12

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 475 publications
(486 citation statements)
references
References 137 publications
(233 reference statements)
8
466
0
12
Order By: Relevance
“…Dam and pond features can alter hydrological regimes, both locally and downstream (Polvi and Wohl, 2012; Burchsted and Daniels, 2014). The resulting increased structural heterogeneity of the environment (Rolauffs et al ., 2001) also creates a diverse range of habitats (Rosell et al ., 2005) with an increasingly recognised potential as a habitat restoration tool (Law et al ., 2017). In addition to increasing biodiversity (Law et al ., 2017), it has been suggested that, due to their engineering activity, beavers could play a role in the management of river catchments (Puttock et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Dam and pond features can alter hydrological regimes, both locally and downstream (Polvi and Wohl, 2012; Burchsted and Daniels, 2014). The resulting increased structural heterogeneity of the environment (Rolauffs et al ., 2001) also creates a diverse range of habitats (Rosell et al ., 2005) with an increasingly recognised potential as a habitat restoration tool (Law et al ., 2017). In addition to increasing biodiversity (Law et al ., 2017), it has been suggested that, due to their engineering activity, beavers could play a role in the management of river catchments (Puttock et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Assuming an average group size of 3.9 (Rosell & Parker 1995;Rosell et al 2005), the results suggest a current territoriallyresident population of about 80 individuals, plus a number of nonterritorial dispersing individuals in any year.…”
Section: Discussionmentioning
confidence: 91%
“…However, the activity of beaver makes water systems healthy and in good condition. Their work is crucial in formation of wetland ecosystems, which in turn is used by many other species (Hägglund and Sjöberg, 1999;Baker et al, 2005;Rosell et al, 2005;Dalbeck et al, 2007;Ciechanowski et al, 2011).…”
Section: Introduction / Uvodmentioning
confidence: 99%